Kepuasan Nasabah Ditinjau Dari Pelayanan Dan Kinerja Karyawan Pada Bank Jateng Cabang Pembantu Syariah Universitas Muhammadiyah Surakarta Tahun 2015 - Munti'ah, Dianatul (2016)
The aim of the research is to know: 1) The influence of the satisfaction of the costumers in university students. 2) The influence of the work of the official employee of the satisfaction of the costumers in university students. 3) The influence of the service and the work concerning to the satisfaction of university students. This research belongs to quantitative research, the conclusion can be drawn through statistic analysis. The population of the research is university students of Faculty of Teacher and Training Education 2011 generation who use the service of Bank Jateng branch of UMS. The sample is taken for 100 students by using accidental sampling. The data that is needed is gotten from questionaire and documentation. The questionaire is tested first and the validity and the reliability are also tested. The technique of analyzing the data that is used is analisis regresi linier berganda, uji T, uji F, and sumbangan relatif dan efektif. The result of regresion analysis obtaines the equation of regresion line: Y = 4, 345 + 0,315X1 + 0,220X2 . The equation shows that the satisfaction of the costumers influenced by the service and the work of the official employee. The conclusion is : 1) Based on the result of analisis regresi linier berganda obtained the cofficient of the satisfaction is 0,411, the service is 0,315 and the work is 0,220. This result shows that the variable of the service and the work of the official employee give influence to the satisfaction to the costumers in university students. 2) From uji T obtained thitung for variable of service is 6,677 whereas ttabel is 2,000, so H0 is rejected. It can be concluded that there is significant influence between the service concerning to the satisfaction individually. It proves that the first hypothesis that states that "There is influence between the service concerning to the satisfaction of university students". 3) From uji t obtained thitung for variable of the completeness of the work of official employee is 2,382 meanwhile ttabel is 2,000, so H0 is rejected. Thus, there is significant influence between the work concerning to the satisfaction of the customers individually. It proves the second hypothesis that states "There is influence between the work concerning to the satisfaction of the customers in university students". 4) From the result of the analysis of tes F obtained that Fhitung = 135,549 > Ftabel = 3,150, so H0 is rejected. Therefore, there is significant influence between the service and the work of official employee to the costumers. From the result, it shows that the third hypothesis states that "The influence of the service and the work concerning to the satisfaction of the costumers in university students".